Fruit, vegetables, and colorectal cancer risk: the European Prospective Investigation into Cancer and Nutrition. - van Duijnhoven, F; Bueno-De-Mesquita, H; Ferrari, P; Jenab, M; Boshuizen, H; Ros, M; Casagrande, C; Tjønneland, A; Olsen, A; Overvad, K; Thorlacius-Ussing, O; Clavel-Chapelon, F; et al. (2009)
BACKGROUND: A high consumption of fruit and vegetables is possibly associated with a decreased risk of colorectal cancer (CRC). However, the findings to date are inconsistent. OBJECTIVE: We examined the relation between self-reported usual consumption of fruit and vegetables and the incidence of CRC. DESIGN: In the European Prospective Investigation into Cancer and Nutrition (EPIC), 452,755 subjects (131,985 men and 320,770 women) completed a dietary questionnaire in 1992-2000 and were followed up for cancer incidence and mortality until 2006. A multivariate Cox proportional hazard model was used to estimate adjusted hazard ratios (HRs) and 95% CIs. RESULTS: After an average follow-up of 8.8 y, 2,819 incident CRC cases were reported. Consumption of fruit and vegetables was inversely associated with CRC in a comparison of the highest with the lowest EPIC-wide quintile of consumption (HR: 0.86; 95% CI: 0.75, 1.00; P for trend = 0.04), particularly with colon cancer risk (HR: 0.76; 95% CI: 0.63, 0.91; P for trend < 0.01). Only after exclusion of the first 2 y of follow-up were these findings corroborated by calibrated continuous analyses for a 100-g increase in consumption: HRs of 0.95 (95% CI: 0.91, 1.00; P = 0.04) and 0.94 (95% CI: 0.89, 0.99; P = 0.02), respectively. The association between fruit and vegetable consumption and CRC risk was inverse in never and former smokers, but positive in current smokers. This modifying effect was found for fruit and vegetables combined and for vegetables alone (P for interaction < 0.01 for both). CONCLUSIONS: These findings suggest that a high consumption of fruit and vegetables is associated with a reduced risk of CRC, especially of colon cancer. This effect may depend on smoking status.